Perlindungan Hukum Korban Terhadap Pelanggaran Hak Privasi Dalam Pembuatan Konten Menggunakan Drone - Nurkamal, Akmal Zulham; Astuti, Laras (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2024)
If drones are new, people have always been concerned about how they can be used for unauthorized stalking, monitoring, or documentation. Unauthorized content creation can be categorized as a cybercrime if the photo or video content contained does not have permission and is misused. This study aims to determine the form of privacy violations related to the use of drones and legal protection for the privacy of victims of misuse of content creation using drones. The research method was carried out using the juridical-normative legal research method. The data used in this study are secondary data sourced from primary and secondary legal materials and interviews as supporting data. The conclusion obtained from the study is that content creation using drones causes various forms of privacy violations and legal regulations that do not specifically regulate the use of drones. The legal protection for victims of violations of privacy rights against content creation using drones is stated in Law No. 1 of 2024 concerning Information and Electronic Transactions which regulates that victims whose rights are violated can sue and receive compensation for the losses incurred and require the perpetrator to delete Electronic Information and/or Electronic Documents in accordance with the provisions of laws and regulations